Analysis of Student’s Difficulties in Translating Argumentative Text - Ginting, Lastry; Harahap, Fitri Ramadani (Journal of Applied Linguistics, 2025)
In this study the objective is identify the difficulties of the students when they translate argumentative text from English to Indonesian, what is the difficulties of the students when they translate the text. This research is done through descriptive qualitative method and the data collected by given the text to the students and the students translate the data. After the data were collected then the writer analyzed the data by elaborated the mistake and difficulties of the students. The result indicates that there are some difficulties that made by the students. Such as when the students translate word to word they still make the mistake because they can’t find the word in the dictionary, the second group to group translation, the students still make the mistake when translate more than one words.  From the percentage of the factors that make the students difficult in translating argumentative text, the students dominant chose often and sometimes in their questionnaire and the average of percentage is 45 % students chose sometimes and 55 % students chose often. It can be concluded that there are still so many students’ difficulties when they translate the English text especially argumentative text. Keywords : Difficulties, Translation, Argumentative text